Sinicization of Western Learning and the Global History of Knowledge: A Case Study of Huang Baijia’s Comment in Song Yuan Xue’An (宗教与历史 （ISSN: 3068-4803）, 2025)
Huang Baijia has made a lengthy comment on meteorological change in Song Yuan Xue’ an, generally, scholars regard it as Huang Baijia’ s own synthesis of western learnings. In fact, Huang’s comment derived from Zhengshi Lüeshuo, which was written by Chinese Catholic scholar Zhu Zongyuan. Zhu’s book is a work of apologetics; it refers to many Jesuits’ books, such as Taixi Shuifa of Sabatino de Ursis, Huanyou Quan of Francisco Furtado, Kouduo Richao of Giulio Aleni, etc. In Huang’s citation, he pruned all the materials relating to Catholicism while sustaining western secular knowledge. Carefully comparing the valuable copies of Chinese Catholic literature, namely, Zhengshi Lüeshuo of Zhu Zongyuan, Tianjiao Mingbian of Zhang Xingyao, and Xingxue Xingmi of Chen Xun, we can clearly see the western origin of Huang Baijia’s comment as well as his alteration. This provides us with a specific case of the circulation, transformation and sinicization of western learning in the early Qing period, as well as the globalization of modern scholarship.